Low-dose spinal anesthesia for cesarean section to prevent spinal-induced hypotension. Issue 3 (June 2019) - Van de Velde, Marc
Abstract : Purpose of review: Low-dose combined spinal epidural (CSE) anesthesia is a common technique to anesthetize women for cesarean section. It is used to reduce the incidence of hypotension while providing excellent anesthetic conditions. Recent findings: Low spinal doses produce effective anesthesia but of limited duration. Therefore, an epidural catheter (and thus CSE) is required to guarantee pain-free surgery. Recent work confirmed that lower spinal doses can reduce significantly hypotension. Summary: Low-dose CSE is a valuable strategy to anesthetize pregnant women for cesarean section but requires attention and training.